Financiamento político por empresas privadas no Brasil: mácula ao exercício da representatividade democrática e desvirtuamento do princípio um cidadão, um voto - Rocha, Rafael Sampaio (2015)
The topic of political reform back to the top of the national agenda and brings with it the need for discussion on how the political funding has tarnished the exercise of democratic representation, especially by misrepresenting a universal premise of democratic systems: the principle of "one citizen, one vote". From the presentation of modern democratic theories and models of analysis of empirical research that portray the feeling of distrust of brazilians as representative democratic institutions, this study will examine the role of political finance in this context configuration. Will be presented the species most common funding, and, after a brief history of political funding in Brazil, will be made a critical analysis about what features the current regulatory system, especially the negative influence of the economic power of private companies in forming the link between political finance and corruption, including examination of specific cases. In the end, will be analyzed the challenges to the regulation of political finance to combat corruption, as well as will be indicated the horizons of Brazilian political finance change, based on the position of the judiciary in ADI 4650 and objectives outlined by the legislature in PEC 182/07 and in PL 5735/13, which are in processing. As will be seen, these two powers are plotting courses diametrically opposed about the permissiveness of corporate donations to political finance, which will be made at the end, a reflection on the following questions: who will have the last word (if it exists) on the course of political finance by private companies in Brazil?